INNOVATIVE STRATEGIES IN DA’WAH MANAGEMENT: HARNESSING SOCIAL MEDIA FOR ISLAMIC OUTREACH - Qomariyah Qomariyah; Ming Kiri; Ananya Rao (Journal International Dakwah and Communication, 2026)
Da’wah has traditionally relied on face-to-face interaction and community-based structures to disseminate Islamic teachings. The rapid expansion of social media has transformed patterns of religious communication, creating new opportunities and challenges for Islamic outreach. This digital shift requires da’wah actors to move beyond conventional approaches and adopt innovative management strategies that align religious objectives with the dynamics of online platforms. This study aims to analyze innovative strategies in da’wah management and to examine how social media is harnessed effectively for Islamic outreach. The research employed a qualitative-dominant mixed-methods design, involving questionnaires distributed to da’wah practitioners, in-depth interviews with managers of Islamic organizations, and a focused case study of social media–based da’wah initiatives. The findings reveal that structured planning, message consistency, and active audience engagement significantly enhance the effectiveness of digital da’wah. However, the use of analytics and systematic evaluation remains limited, indicating gaps in data-driven management practices. The study concludes that social media–based da’wah can achieve sustainable impact when managed strategically, ethically, and responsively to platform characteristics. Integrating management principles with Islamic values is essential to strengthening the credibility and long-term effectiveness of digital Islamic outreach in the contemporary media landscape.